Respuesta :

Answer:

h(-3)=-1

Step-by-step explanation:

Replace all x in h(x)= -3x-10 by -3:

h(-3)=-3(-3)-10

Now multiply -3 and -3:

h(-3)=9-10

Simplify 9 and -10 (aka add 9 and -10 together):

h(-3)=-1

Answer: h(-3)=-1

Hope this helps!

Answer:

-1

Step-by-step explanation:

If h(x)= -3x-10 and we want to solve for h(-3) then we have to plug in -3 for all x variables. h(-3)= -3(-3)-10, then solve using PEMDAS.

First multiple h(-3)= 9-10, multiple -3*-3 to get 9.

Then subtract, h(-3)=-1